Child Education from Islamic and Western Perspectives - Azka Salsabila, Puteri; Anwar, saiful; Huwaida, Jaziela (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2024)
Child education is a crucial aspect of individual and societal development. This study discusses and compares the concepts of child education from Islamic and Western perspectives, focusing on educational objectives, teaching methods, and the role of teachers. The background of this research stems from the need to understand the differences and similarities between these two approaches to create a more holistic and inclusive educational system. This research employs a library research method, gathering data from various relevant primary and secondary literature, including books, academic journals, and research articles. Data analysis is conducted descriptively and comparatively to identify the main themes, differences, and similarities in child education concepts from both perspectives. The findings indicate that child education from the Islamic perspective emphasizes character and spirituality formation, while Western education focuses more on developing critical thinking skills and active participation in society. Teaching methods in Islam are holistic, emphasizing moral and spiritual education, whereas Western education employs student-centered and interactive approaches. The role of the teacher in Islamic education is more of a moral exemplar and authoritative figure, whereas in Western education, the teacher acts as a facilitator supporting student exploration. The conclusion of this research is that integrating Islamic and Western educational approaches can result in a more comprehensive educational system, which not only develops the intellectual aspects but also the moral and spiritual aspects of children. Therefore, it is recommended to develop curricula and teaching methods that combine the moral values of Islamic education with the critical and creative approaches of Western education. Adequate teacher training is also essential to support the implementation of a holistic and student-centered educational approach.